2011
DOI: 10.4028/www.scientific.net/kem.466.1
|View full text |Cite
|
Sign up to set email alerts
|

Concrete-Polymer Composites – The Past, Present and Future

Abstract: The present paper deals with the principles of process technology for concrete-polymer composites, the research and development history of the concrete-polymer composites, the recent trends in the research and development of the concrete-polymer composites and the present status of major standardization work for the concrete-polymer composites, on the basis of comprehensive literature survey. The future trends in the research and development of the concrete-polymer composites are predicted, and sustainable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 40 publications
0
15
0
3
Order By: Relevance
“…Figure 11. Relationship of spacing factor and water absorption of LWA [16] The X-ray and neutron tomography study of internally cured cement paste by expanded clay demonstrated that internal curing water was the passage to at least 3 mm [18]. Micro-tomography of X-ray mortars internally cured through extended shale confirmed that internal curing water immigrates to the space of about 2 mm [4].…”
Section: Discussionmentioning
confidence: 90%
“…Figure 11. Relationship of spacing factor and water absorption of LWA [16] The X-ray and neutron tomography study of internally cured cement paste by expanded clay demonstrated that internal curing water was the passage to at least 3 mm [18]. Micro-tomography of X-ray mortars internally cured through extended shale confirmed that internal curing water immigrates to the space of about 2 mm [4].…”
Section: Discussionmentioning
confidence: 90%
“…Concrete technology uses fibers to strengthen concrete structures; the major increase in compression strength has increased its importance worldwide. They use this technology and adapt it in different shapes, sizes, and colors for many building applications (Ohama, 2011;Sabnis, 2012). A feasibility study was conducted for recycling nylon fiber in concrete.…”
Section: Research Articlementioning
confidence: 99%
“…The chloride ion penetration or the use of alkali-reactive aggregates in the reinforced concrete structures were proved to be the major causes of premature corrosion of reinforcing bars and their deteriorations. Consequently the development of effective protection or repairing materials for the reinforced concrete structures is required in the construction industry (Ohama 2006;Ohama and Demura 2010). The use of ultrarapid hardening cement can make strength development rate increase.…”
Section: Introductionmentioning
confidence: 99%